Practicum Activities in the Field of Natural Science Learning in Elementary Schools as an Alternative to the Open Natural Science Laboratory - Mohammad Imam Sufiyanto; Roychan Yasin (Unversitas Muhammadiyah Mataram, 2021)
Abstract: The purpose of this research is to find out in science learning that it does not have to be theoretical, but also practical even during a pandemic. The research method is to use a qualitative research method with the phenomenology approach, namely looking at some natural facts that occur in natural events. The results of the study showed that students can be invited to practice in real, concrete, in accordance with the theory being studied (in the context of SD science, namely about the condition of the surrounding environment, or in everyday life). The problems that exist in the field are, in fact, some of the teachers only teach a few theories in the book and only apply lessons in the classroom. This is triggered by the absence of adequate laboratory facilities at schools, and the lack of motivation to make learning innovations that can be carried out during the pandemic so that it is lacking in generating practices and theories that can be implementedAbstrak: Tujuan dari penelitian ini yaitu mengetahui pada pembelajaran IPA bahwa tidak harus dengan teori saja, tetapi juga dengan praktik meskipun di masa pandemi. Metode Penelitian adalah menggunakan metode penelitian kualitatif dengan pendekatan phenomenology yaitu melihat beberapa fakta alami yang terjadi pada kejadian alam. Hasil Penelitian yaitu Peserta didik dapat diajak melaksanakan praktik secara riil, konkrit, sesuai dengan teori yang sedang dipelajari (Dalam konteks IPA SD yaitu tentang keadaan lingkungan sekitar, atau yang ada di kehidupan sehari-hari). Permasalahan yang ada di lapangan, pada kenyataanya, sebagian dari guru hanya mengajarkan beberapa teori yang ada di dalam buku dan hanya menerapkan pembalajaran di dalam ruang kelas. Hal tersebut dipicu karena tidak adanya fasilitas laboratorium yang memadai di sekolah, serta minimnya motivasi untuk membuat inovasi pembelajaran yang dapat dilakukan dimasa pandemic sehingga kurang dalam memunculkan praktik dan juga teori yang dapat dijalankan.